MENINGKATKAN KEMAMPUAN PRESENTASI AKADEMIK DOSEN STIKES MELALUI PELATIHAN ENGLISH FOR ACADEMIC PRESENTATION - Dwi Iswati, Henny; Chakim, Nur; Lolita, Yuri; Ramadhan, Riski; Abdullah, Muhaimin (Universitas Negeri Surabaya, 2025)
The training on English for Academic Presentation for professional lecturers at STIKES William Booth Surabaya aims to enhance academic presentation skills in English, enabling lecturers to participate more actively in international seminars. The methods used include structured training, presentation simulations, and feedback sessions for participants. This training covers various aspects such as material preparation, grammar, pronunciation, and presentation style. The results of this training indicate an improvement in the lecturers' presentation skills, including material clarity, grammatical accuracy, better pronunciation, and a more professional and effective presentation style. With this training, it is expected that lecturers will be more confident and competent in delivering presentations at international forums, thus supporting their professional development and enhancing the academic reputation of the institution. Additionally, this training serves as an effort to strengthen lecturers' capabilities in global scientific communication, which is crucial in the current era of higher education globalization. Evaluations conducted through direct monitoring and feedback collection show that participants become enthusiastic and prepared to face international seminars. The program also provides activity documentation in the form of photos and videos uploaded on YouTube for further reference. Keywords: Presentation Training, English Academic Presentation, Professional Lecturers, International Seminars, Higher Education Globalization